DEVELOPMENT OF AN ENGLISH E-MODULE BASED ON RELIGIOUS MODERATION THROUGH THE POWTOON APPLICATION - riani, novi; Opi Teci Darisma Putri (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This research aims to develop an English E-Module based on religious moderation through the powtoon application. This type of research is development research wuth the ADDIE development model. The data analysis technique used qualitative and quantitative. The results showed 1) Development of an English E-Module based on religious moderation with the help of Powtoon using the ADDIE development model through 5 stages: Analyze, design, development, implementation and evaluation. 2)Based on the research results, it was successfully developed with a very valid category according to the assessment results of the three validators, namely media experts, material and language experts with scores of 82.5% each, 78.9 % and 95 %, with an average percentage score of 85.4 % in the very valid category. 3) Based on the results of the student's mawaris understanding ability test, a percentage score of 85.07% was obtained in the high category. This proves that the E-Module developed is by students' understanding abilities. Keywords: English E-Module, Religious Moderation, Powtoon Application